(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, it is substantiated the importance and relevance of the study of discourse in general and literary- and- artistic discourse in particularly, theoretical issues of understanding the concept of literary and artistic discourse in modern science and highlighted, an overview of various scientific concepts in the field of the study of discourse.